^=exponent X=multiply x=variable 4^(-2) 4^(-3)-4^(0) Solve for x: 3^(2x+1-x+2)=3^(x2-x) Anyone know how to solve these???
Follow Math Help Forum on Facebook and Google+
Remember that x^(-1) = 1/x Also remember that x^0 = 1 so 4^(-3) = 1/(4^3) And 4^(-2) 4^(-3)-4^(0) can be rewritten as 1/16 1/64-1 can you take it from there?
3^(2x+1-x+2)=3^(x2-x) take log_3 of both sides to render the equation 2x+1-x+2 = x2-x, did you mean x^2 instead of x2 anyway you can take it from here I'm sure.
BTW we usually use * for multiply to avoid confusion with the variable x you can also learn latex and write stuff like this click on it to find out what I did.
Thnx
View Tag Cloud